1987
DOI: 10.1007/bf00405283
|View full text |Cite
|
Sign up to set email alerts
|

Environmental monitoring of mutagenic/carcinogenic hazards during road paving operations with bitumens

Abstract: Environmental monitoring of mutagenic/carcinogenic hazards associated with occupational exposure to bitumen fumes was performed during road paving operations. Bitumen samples were collected and analysed for polycyclic aromatic hydrocarbons (PAH) content by HPLC and for mutagenicity by the Ames test. The exposure of sixteen road workers to bitumen fumes was studied. Time-weighted average values of bitumen fumes were determined by personal samplers. PAH concentration in the air and the mutagenicity of airborne p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Nitrogen-, sulfur-and/or oxygen-containing PAH or their alkyl-substituted analogues may also contribute to genotoxic effects (7,8). The urinary metabolite of pyrene, 1-hydroxypyrene (1-OHP), showed a moderate association with exposure to asphalt fumes (9)(10)(11)(12) and thus may serve as a marker of internal exposure not only to PAH but also to bitumen.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen-, sulfur-and/or oxygen-containing PAH or their alkyl-substituted analogues may also contribute to genotoxic effects (7,8). The urinary metabolite of pyrene, 1-hydroxypyrene (1-OHP), showed a moderate association with exposure to asphalt fumes (9)(10)(11)(12) and thus may serve as a marker of internal exposure not only to PAH but also to bitumen.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they can be expected to be chemically similar to bitumen (Monarca et al 1987a), but they occur simultaneously with aggregate dust, solvents, additives, diesel, and other automotive exhaust. Asphalt is a mixture of bitumen and mineral matter such as stone, sand, or filler.…”
Section: Exposure Types and Levels In Road Construction Industrymentioning
confidence: 98%
“…Twenty epidemiologic studies have dealt with the cancer risk in asphalt workers and roofers (Monarca et al 1987b). These studies nevertheless have limitations, and conclusions on the specific causes of the observed excess cancer risk remained conjectural.…”
Section: Biological Exposure Of Bitumen Fumesmentioning
confidence: 99%
“…In fact, several carcinogenic or cocarcinogenic constituents have been discovered in these products. A number of authors have shown the presence of polycyclic aromatic hydrocarbons (PAHs), some of which are known to be carcinogenic or cocarcinogenic (Bingham et al, 1979;IARC, 1983), in working operations with mineral oils, tar, pitch, and bitumens (Guerin et al, 1978;Hueper and Payne, 1960;Kipling and Waldron, 1976;Lindstedt and Sollenberg, 1982;Monarca et al, 1982Monarca et al, ,1984Monarca et al, ,1987Peake and Parker, 1980;Thayer et al, 1983;Thony et al, 1975). In particular, PAHs are concentrated in the highest boiling point distillates and in the solid residues obtained from petroleum processing.…”
Section: Introductionmentioning
confidence: 96%